UJI KINERJA ALAT IRIGASI SPRINKLER TIPE BIG GUN 1,25 INCI DI DESA TONTALETE KECAMATAN KEMA KABUPATEN MINAHASA UTARA - Novianti Nari; Ruland A. Rantung; Dedie Tooy (Universitas Sam Ratulangi, 2021)
Abstract Sprinkler irrigation is the provision of water to crops by spraying water into the air, so that the plants get water from above like rain. The principle used by this system is to put pressure on the water in the pipe and emit it into the air so that it resembles rain and then falls on the ground. The purpose of this study is to test the performance and calculate ef iciency and uniformity of water supply by using irrigation sprinkler of the type big gun 1.25 inch. The method used is an experimental method and a descriptive analysis method, which focuses on performance testing using a irrigation unit sprinkler of type Big Gun 1.25 inch. This study uses several components of equipment such as a spinkler, water pump and hose on the plantation land of Tontalete Village with an area of 40 m x 40 m. The variables observed in this study include: water discharge, pump rotation (rpm), uniformity coef icient (CU), jet distance, and pump fuel use. The results of this study indicate that the provision of irrigation water sprinkler using a sprinkler Big Gun 1.25 inch and MGP pump 50 HD, with a round of sprinkler 3 times round the that produces a time for 12 minutes, the sprinkler can remove as much water as 77.46 l / min and irrigate the land area of 1,017 m2 with an average speed of rotation pump 2,008 rpm and spent as much as 280 ml of pump fuel/12 minutes. The farthest distance thewater sprinkler emits is 18 m. Keywords: performance test, irrigation, sprinkler, radiance, water discharge